Horn symphony : A collection of compositions especially adapted for horn ensemble and recomended for class work - HOLMES, G.E. (Rubank Inc., 1939)
Album leaf.....R. SchumannnAutumn......Bohemian folk songnChild's prayer....T. KullaknChoral.....J.S. BachnChoral from the meistersinger.........R. WagnernCradle song..............M. Hauser